Revision of the genus Trichophallus Ingrisch, 1998 with notes on the genera Secsiva Walker, 1869 and Subrioides C.Willemse, 1966 (Orthoptera: Tettigoniidae: Conocephalinae: Agraeciini) - Ingrisch, Sigfrid (Zootaxa, 2024)
The Papuan genus Trichophallus Ingrisch, 1998, mainly found in New Guinea and some neighbouring Islands is revised. The study is based on historical but formerly unworked specimens found in museum collections of North America, Europe, and Indonesia. The differentiation between the genus Trichophallus and the superficially similar genera Subria Stål, 1874, Secsiva Walker, 1869, and Subrioides C. Willemse, 1966 are outlined and discussed. Important characters to differentiate Trichophallus from other similar genera are found in a combination of the shape of the fore wings, the absence of prosternal spines, and the male titillators being provided with tufts of hairs apart from sclerites. The female ovipositor carries a pair of sub-basal, lateral lobes, so far unknown from other genera of Tettigoniidae, and the female subgenital plate is provided with a pair of basal, dorsal-lateral extensions often larger than the ventral area of the subgenital plate. 19 species and one subspecies are described as new, all from New Guinea or nearby islands. T. tricuspis Naskrecki & Rentz, 2010 is removed from Trichophallus and newly combined with the genus Subrioides. Keys to the species of Trichophallus are provided.